The effect of psychological contract towards deviant behaviour, employee engagement and employee commitment - Ismail, Fadillah; Juhari, Nurhannani; Mohammed Al-Qershi, Nagwan Abdulwahab; Imran, Muhammad; Alhosani, Adnan Ali Hassan; Jaes, Lutfan (2022)
Psychological contract plays an important role in the human resource management of the organization. Development and technology can bring bright future to the organization but at the same time can disturb employee and employer relationship due to the wide use of technology replacing human labour which automatically reducing employee contribution in the work process. Therefore the purpose of this research is to measure the level of psychological contract, to determine there any relationship between psychological contract on deviant behaviour, employee engagement and employee commitment, and to examine the impact of psychological contract toward deviant behaviour, employee engagement and employee commitment among employee at MBXX. Quantitative research approach along cross-sectional research design has been used to collect 205 data from MBXX in target population through a self-administered questionnaire. The results of the current study provide empirical evidence on key issues related to psychological contract of employees at MBXX. Finding have shown, the deviant behaviour, employee engagement and employee commitment were in a high, moderate, and low level and there is positive relationship between the performance psychological contract, employee engagement (r=0.331), and employee commitment (r=0.411), while deviant behaviour is not significant (r=-0.178). This study also proved that psychological contract has significant effect towards deviant behaviour (r2=0.025), employee engagement (r2=0.000), and employee commitment (r2=0.00). Conclusion, this research gives clear direction to organization the existing psychological contract employee for improvement of the deviant behaviour, employee engagement, and employee commitment at government sector or other private sectors.